The first of the modern Ottomans the intellectual history of Ahmed Vasif /cEthan L. Menchinger - Menchinger, Ethan L. (Cambridge University Press, 2017)
This book explores intellectual life, politics and reform in the eighteenth-century Ottoman Empire by studying statesman and historian Ahmed Vâsıf